When superhydrophobic coatings are icephobic : role of surface topology - Chen, Zhong (2019)
Among different types of anti-icing coatings, superhydrophobic coatings have attracted considerable attention due to their water repellency and low heat-transfer rate. However, condensation on superhydrophobic surfaces at low temperatures usually causes an increase in ice adhesion because of the induced wetting of micro- and nanostructures. By tuning the weight ratio of surface-modified nanoparticles to unmodified ones, five superhydrophobic coatings with different structural features at the microscale were developed. Ice-adhesion strength and ice-nucleation temperature were studied, together with the effect of moisture condensation on ice adhesion. It was found that the ice-adhesion strength and icing temperature of these coatings do not necessarily follow the same order among these surfaces because of different mechanisms involved. Surface roughness is inadequate to describe the necessary surface features that critically affect the anti-icing behavior of the coatings. Detailed topology/geometry has to be considered when designing icephobic coatings. Superhydrophobic coatings can be adopted for icephobic applications once the surface topology is carefully designed.